MAYER-ROKITANSKY-KÃœSTER-HAUSER SYNDROME: MR MANIFESTAIONS OF TYPICAL AND ATYPICAL CASES - Nasir Khan,; Maria Khaliq,; Madiha Maryam Azam,; Riffat Raja, (Journal of Ayub Medical College Abbottabad, 2021)
Background: The Mayer-Rokitansky-KÃ¼ster-Hauser (MRKH) syndrome is a group of congenital malformations arising due to agenesis or arrest of the growth of paired Mullerian ducts leading to absence of uterus, fallopian tubes and upper part of vagina. MRI has an unmatched role in diagnosing MRKH syndrome. The aim of the present study is to elaborate MRI manifestations of typical and atypical MRKH syndrome and its common and rare associations. Methods: It was a cross sectional analysis of 19 cases in the Radiology Department of a public sector tertiary health care hospital of Rawalpindi over a period of one year. All patients clinically diagnosed as MRKH syndrome were included in the study. MRI pelvis of the study patients was performed and evaluated by two experienced radiologists. Results: The mean age of study patients was 22.2 years. Out of 19 study patients, 16 (84%) had type I while 3 (16%) had type II MRKH syndrome. None of the patients had normally cited uterus of normal morphology. Bilateral ovaries with follicular activity were identified in all patients. A well-defined leiomyoma was identified arising from the left uterine bud in one of these patients. All three patients with MRKH II syndrome had ectopic pelvic kidneys. One of the patients showed a neoplastic mass lesion arising from ectopic left kidney. Conclusion: MRI is an excellent imaging modality for accurate diagnosis and evaluation of other system anomalies in MRKH syndrome. Rudimentary uterine buds are commonly seen in these patients and may have functioning endometrium. Ovaries are of normal appearance but frequently ectopic.